The Influence of the Learning Environment on the Learning Achievement of Students of SMK Negeri 1 Wajo - Besse Fahmy Wahyuni; jamaluddin Jamaluddin; Sitti Hardiyanti Arhas (ASHA Publishing, 2024)
Learning achievement is the outcome achieved by students consisting of knowledge, skills and attitudes as a result of experience and education received individually. Success can be achieved through the learning activities carried out. Learning achievement is the level of success in learning, it is one way to measure how well students participate in education in school. Learning and the environment are two things that cannot be separated from each other, the learning environment is the place where learning takes place and externally affects the continuity of activities. This study discusses how the learning environment affects the learning outcomes of SMK Negeri 1 Wajo students. This research is quantitative showing cause and effect. The sample in this study is 90 samples with a simple random sampling technique. Data collection techniques are carried out using questionnaires, observations and documentation. The data analysis techniques used are descriptive data analysis and inferential statistical analysis. The results of the study show that the learning environment in the teaching and learning process of SMK Negeri 1 Wajo is in the